Mitigation of faults in grid-connected wind-driven single machine brushless double-fed induction generator - Maged Naguib Nashed; Mona Naguib Eskander; Mahmoud Saleh (Institute of Advanced Engineering and Science, 2019)
The effect of three-phase grid fault on the performance of a wind-driven single machine-brushless double fed induction generator (SM-BDFIG) is investigated. The fault-ride-through (FRT) of the grid-connected SM-BDFIG is then studied when installing a Static Synchronous Compensator (STATCOM) between the grid and the generator. Recovery from the grid fault before installing the STATCOM is studied and compared to the generation system recovery with installed STATCOM. The performances of the stator and rotor currents, stator and rotor voltages, electric torque, active power, reactive power, and battery pack voltage and current are presented for both cases. The total harmonic distortion (THD) of stator and rotor voltages and currents are also presented and compared. Results proved the faster recovery from grid faults, the continuity of currents and voltages, and the continuity of active power supplied to the grid when installing the STATCOM. However, slightly higher THD took place in the stator and rotor voltages and currents due to the switching pattern of the STATCOM.